Junior High School Science Teachers Supporting Independent Curriculum Transition: Guru Ilmu Pengetahuan Alam Sekolah Menengah Pertama Mendukung Transisi Kurikulum Mandiri - Eva Susiana Agustin; Septi Budi Sartika (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Educational reform in Indonesia has introduced the Merdeka Curriculum, requiring substantive adjustments in teaching practices at the junior high school level. Specific Background: Science learning under this curriculum emphasizes student-centered approaches, differentiated learning, and character development aligned with the Pancasila Student Profile, positioning science teachers as key actors during the transition period. Knowledge Gap: Empirical evidence detailing how junior high school science teachers enact their roles during the Merdeka Curriculum transition remains limited, particularly within specific school contexts. Aims: This study aims to analyze the roles of science teachers in facilitating the transition to the Merdeka Curriculum at SMP Muhammadiyah 1 Sidoarjo. Results: Using a qualitative case study design with observation, documentation, and interviews, the findings indicate that science teachers have understood and implemented the curriculum, acting as facilitators, motivators, and innovators. Supporting infrastructure, differentiated instruction, and inter-teacher collaboration supported implementation, while differences in student mindsets were identified but did not substantially obstruct learning processes. Novelty: The study provides contextualized insights into science teacher practices during the early phase of Merdeka Curriculum implementation in a junior high school setting. Implications: These findings underscore the central role of science teachers in curriculum transition processes and offer practical considerations for schools and policymakers in supporting curriculum adaptation and character-oriented science learning. Highlights: Science educators demonstrated curriculum comprehension and active classroom application during the transition phase. Institutional facilities and collegial collaboration supported differentiated science learning practices. Variations in learner mindsets emerged but did not constitute major obstacles in classroom implementation. Keywords: Science Teacher, Merdeka Curriculum, Differentiated Learning, Curriculum Transition.